Perspektif Ibu-Ibu Indonesia tentang Kesehatan Anak Setelah Persalinan Sesar: Sebuah Eksplorasi Deskriptif: Indonesian Mothers’ Perspective on Children’s Health After Caesarean Delivery: A Descriptive Exploration - Munasir, Zakiudin; Darus, Febriansyah; Kinesya, Edwin; Kartjito, Melissa Stephanie; Sundjaya, Tonny (Universitas Airlangga, 2025)
Background: Cesarean section incidence increases over time in both emergency and elective cases, or with medical indication and social factors. Despite the usefulness of C-section, parents need to be aware of its effect to child health and the countermeasure. Objectives: This study aims to explore mothers’ perspectives about the health effects of C-section to children. Methods: An open-ended survey was conducted on Indonesian mothers as participants in a cross-sectional study. A compilation of descriptive responses was collected at an online parenting community focused on children’s health. The questions are later classified into six particular categories and given an analysis. Results: A total of 175 inquiries were collected and categorized into 6 groups. In declining pattern, we found parental concern regarding the effect of C-section on the child's immune system (57.14%), nutrition and prebiotics/ probiotics/ synbiotic (22.28%), growth and development (8%), and gastrointestinal system (6.28%). A total of 42 questions (24%) can be categorized into more than one category. Conclusions: More than half of parents are concerned about the effect of C-section on children’s immune system, and one out of five mothers is concerned about the role of nutrition for their children’s health. However, the awareness and concern regarding C-section health impact on growth and development, and gastrointestinal system are still very low.